Comorbidity in the aging population with multiple sclerosis: a Danish nationwide study - Holm, Rolf Pringler; Wandall-Holm, Malthe Faurschou; Sellebjerg, Finn; Magyari, Melinda (Frontiers in Neurology, 2023)
Introduction Multiple sclerosis (MS) is a neurodegenerative disease accumulating disabilities over time. However, the mean age of individuals with MS is increasing, consequently elevating their risk of developing comorbidities. Comorbidities' impact on MS is widely debated. Yet very few countries possess population-based registries, which provide unique opportunities for individual-level data linkage. This study aims to assess acute and chronic comorbidities among elderly patients with MS, comparing them to matched controls. Additionally, this study seeks to investigate the influence of chronic comorbidities on all-cause mortality. Methods A nationwide register-based study using the Danish Multiple Sclerosis Registry to identify all living patients with MS older than 50 years at the reference date (January 1st, 2022). Patients were matched 1:10 with individuals from the general population. Comprehensive healthcare data within the Danish hospital system were obtained. Chronic comorbidities were classified according to the Charlson Comorbidity Index, while acute comorbidities were based on ICD-10 codes and an “acute” admission type. To investigate all-cause mortality, a Cox regression analysis was conducted. Results The study encompassed a total of 8,688 individuals with MS, matched with 86,880 controls. The mean age was 63.5 years, with females constituting 68.3%. Individuals with MS exhibited a higher frequency of acute hospitalizations (OR: 2.1, 95% CI: 1.9–2.2), primarily due to various infectious diseases, along with longer median hospital stays (4 vs. 3 days, p < 0.001). When assessed using the Charlson Comorbidity Index, individuals with MS carried a significantly greater burden of chronic comorbidities (p < 0.001). The most prevalent chronic comorbidity among individuals with MS was “Uncomplicated Diabetes” (20.1%). Notably, while individuals with MS displayed an overall lower 5-year survival rate, this difference ceased to be statistically significant among those with a high Charlson Comorbidity Index score of ≥4 (p = 0.32). Conclusion This study highlights a heightened prevalence of both acute and chronic comorbidities among individuals with MS, with chronic comorbidities significantly increasing the risk of mortality. These findings underscore the critical importance of factoring in comorbidities when devising treatment strategies for individuals living with MS.